2022
DOI: 10.3126/mjmms.v2i3.47752
|View full text |Cite
|
Sign up to set email alerts
|

Exemplification of ABO Blood Groups in Patients with Diabetes Mellitus

Abstract: INTRODUCTION: Diabetes Mellitus and blood groups are interrelated. The relationship between ABO blood groups and disease susceptibility has generated a concern. The identification of a positive relationship between DM and blood groups could indicate higher susceptibility to diabetes and a negative relationship could indicate protection from diabetes. Therefore, the objective of the study was designed to exemplify ABO blood groups in Patients with Diabetes Mellitus. MATERIALS AND METHODS: The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
3
0
1
Order By: Relevance
“…In contrast to our findings, previous studies in Italy and Trinidad reported a higher prevalence of the B blood group among diabetic patients [24]. It was found that B blood group was more prevalent among diabetic patients [25]. It is believed that there is a connection between blood groups and type 2 diabetes due to shared genetic and immunologic factors [26].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, previous studies in Italy and Trinidad reported a higher prevalence of the B blood group among diabetic patients [24]. It was found that B blood group was more prevalent among diabetic patients [25]. It is believed that there is a connection between blood groups and type 2 diabetes due to shared genetic and immunologic factors [26].…”
Section: Discussioncontrasting
confidence: 99%
“…It accounted for 35.71% of cases, whereas in the control group, it was only 22.52%. This pattern of blood group B being more prevalent among diabetes mellitus patients has also been observed in other studies [25,32]. It is worth noting that, in the Malaysia study, this difference compared to the control group was not statistically significant.…”
Section: Discussionsupporting
confidence: 85%
“…Our results demonstrated that diabetes has a high prevalence in patients over 50 years of age, these results corroborate a recent study that analyzed 579 diabetic patients and showed that the highest prevalence was between 40 -60 years of age [26]. The same study revealed that blood group B has the highest frequency (42%), followed by blood group AB (23%), O (21%), and A (11.4%), respectively, while in our study the highest frequency was observed in blood group O (44%), followed by groups A (27%) and B (23%) respectively [26].…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that diabetes has a high prevalence in patients over 50 years of age, these results corroborate a recent study that analyzed 579 diabetic patients and showed that the highest prevalence was between 40 -60 years of age [26]. The same study revealed that blood group B has the highest frequency (42%), followed by blood group AB (23%), O (21%), and A (11.4%), respectively, while in our study the highest frequency was observed in blood group O (44%), followed by groups A (27%) and B (23%) respectively [26]. Researchers from different countries found a diverse association between ABO blood groups and DM, this can be explained by the different distribution of blood groups in the population of these countries and varies according to the population [27,28].…”
Section: Discussionsupporting
confidence: 92%